Peran Protokol dan Komunikasi Pimpinan dalam Mendukung Program Pembangunan Daerah di Kota Bukittinggi - Stevani Novalia (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to describe the role of the Protocol and Leadership Communication Division (Prokopim) in supporting regional development programs in Bukittinggi City. A qualitative descriptive method was applied through observation, documentation, and direct involvement during the internship. The findings reveal that Prokopim plays a strategic role not only in protocol activities but also as a public communication hub that conveys development messages, builds the government’s positive image, and bridges interactions between local leaders and the community. The integration of Islamic economic values such as trust (amanah), justice, and public benefit (maslahah) is reflected in its administrative practices. Nevertheless, challenges remain, including limited human resources, communication facilities, and the gap between ceremonial aspects and substantive policies. Thus, Prokopim is crucial in realizing transparent, participatory, and community-oriented development communication.